1987
DOI: 10.1017/s0021859600079326
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nitrogen, phosphorus and potassium application on yield of potato tubers (Solatium tuberosum L.)

Abstract: SummarySix field experiments, three each during 1982–3 and 1983–4, were conducted on a sandy loam soil to study the effect of varying levels of nitrogen, phosphorus and potassium, in the absence and presence of farmyard manure (FYM) (30 t/ha), on the number of tubers and yield of potato in three grades. Increase in nitrogen, phosphorus and potassium application, in the absence or presence of FYM, did not significantly affect the total number of tubers/m2 but did affect the number of tubers in different grades.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
22
1

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 6 publications
8
22
1
Order By: Relevance
“…Leaf weight was increased significantly from 45 to 75 days. Sharma and Arora (1987) have reported similar results. Increase in P and K had no prominent effect on fresh weight of leaves.…”
Section: Effect On Fresh Weight Of Leavessupporting
confidence: 61%
“…Leaf weight was increased significantly from 45 to 75 days. Sharma and Arora (1987) have reported similar results. Increase in P and K had no prominent effect on fresh weight of leaves.…”
Section: Effect On Fresh Weight Of Leavessupporting
confidence: 61%
“…In addition, under-or oversupply of N may affect total number of tubers (O'Brien, Allen, and Firman 1998). Applications of K fertilizer only affected the number of tubers on very low index soils (O'Brien, Allen, and Firman 1998), and Sharma and Aroma (1987) found that an increase in N and K significantly decreased the number of tubers m -2 in small (<25 g) grades and increased the number in medium (25-75 g) and large (>75 g) grades at 45, 60, 75, and 90 days after planting.…”
Section: Introductionmentioning
confidence: 99%
“…It is predicted from the results that variety Senna-Red produce maximum tuber weight as compared to other genotypes. [28,3] reported that it might be due to increase in weight of tuber nitrogen being the constituent of chlorophyll, promoted cell division and cell elongation, functional life of plant and production of carbohydrate.…”
Section: Diameter Of Tuber (Cm)mentioning
confidence: 99%
“…Its growth, yield and quality largely depend on soil and climatic condition as well as on different production practices. Available reports indicate that the yield of potato increased substantially through adequate application and judicious management of fertilizers [3]. It is mainly produced on coarse textured calcareous soils in arid land and under center pivot irrigation systems.…”
Section: Introductionmentioning
confidence: 99%